Impact of Estimated Pre-Exposure Prophylaxis (PrEP) Adherence Patterns on Bone Mineral Density in a Large PrEP Demonstration Project - Matthew A. Spinelli (2019)
Bone mineral density (BMD) declines due to tenofovir-containing pre-exposure prophylaxis (PrEP) have varied among PrEP demonstration projects, potentially related to variable adherence. Characterization of BMD changes in highly adherent individuals, estimated via tenofovir-diphosphate (TFV-DP) levels in dried blood spots (DBS), can assist clinicians when counseling patients. Cisgender men who have sex with men and transwomen in the optional dual-energy X-ray absorptiometry (DXA) substudy of a large, international, open-label PrEP demonstration project, the iPrEx-open-label extension (OLE) study underwent DXA scans and DBS collection every 24 weeks, with average weekly dosing adherence patterns (2, 4, and 7 doses/week) estimated from validated TFV-DP cut-offs. The mean percent BMD change was estimated in strata of average weekly adherence by using a linear mixed-effects model to calculate the BMD decline in highly adherent individuals on PrEP for the first time. DXA/DBS data were available for 254 individuals over a median of 24 weeks in iPrEx-OLE from June 2011 to December 2013. The percent decline in spine BMD was monotonically associated with strata of increasing average weekly adherence (p < .001 trend); the p value for trends using hip BMD measurements was .07. Individuals with estimated daily adherence experienced a 1.2% decrease in spine BMD and a 0.5% drop in hip BMD. In highly adherent PrEP users, we found a lower-than-expected drop in BMD when compared with previous studies. This drop is likely not clinically significant for most PrEP users. However, for those at the highest risk of fracture who plan prolonged PrEP use, alternate PrEP strategies could be considered.